The Politeness Strategies of Negation Used by English and Buginese - Daud, Najmiah (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
A good communication is a cooperate communication, but when someone wants to deny someone or something, it can be FTA (Face Threatening Acts) in some situations, so she/he needs to express it in polite way to save the face of each through the use of the politeness strategies. This research is aimed to investigate (1) the politeness strategies used by Buginese and American people in using the negation expression; (2) the influence of social and cultural relationship on the politeness strategies used by the Buginese and American people when using negation expression. This was a comparative study between Buginese and English language in using negation. The research used the qualitative descriptive approach. English and Buginese data were obtained through DCT, questionnaire. The research result indicates that three politeness strategies are used by American and Buginese people in using negation namely: the bald on record, positive politeness, and negative politeness. The American people tend to use those strategies in polite way to negate something by being more friendly and using the casual language with other people. On the other hand, Buginese people tend to use formal language as the politeness strategies in making negation. The significant differences between both languages can be seen from the indirect and direct strategies in making negation. English tends to use direct strategies, while Buginese tends to apply indirect negation. The research also indicates that the other aspects influencing the politeness strategies used are; gender, social situation, social distance or intimacy, social status, relationship between interlocutors. Buginese people indicate the politeness by giving the formal treatment because they are more hierarchical and pay more attention to use honorific address term and politeness marker such as iye’. On the other case, American people are more friendly and emphasize the solidarity. Keywords: Politeness Strategies, Negation, Face Threatening Acts.